Association between Emotional State Changes in Infertile Couples and Outcome of Fertility Treatment - Gabnai-Nagy, Erika; Bugán, Antal; Bodnár, Béla; Papp, Gábor; Nagy, Beáta Erika (Geburtshilfe und Frauenheilkunde, 2020)
Aims Infertility and its treatment are associated with considerable psychological distress for infertile couples. The aim of our study was to explore to what extent positive and negative affectivity and a predisposition to depression and anxiety appear in infertile couples during in vitro fertilization (IVF) treatment. We also aimed to explore how the emotional state of couples changed during IVF in relation to treatment outcomes.Method In our longitudinal study, 174 people (87 couples) were followed up during treatment by means of questionnaires. Their emotional state was assessed with PANAS, BDI-R, and STAI at the beginning of treatment, before embryo transfer, and before taking a pregnancy test. Couples who achieved pregnancy after treatment were included in the successful group (n = 82), while those who did not were included in the unsuccessful group (n = 92).Results We found more favorable emotional states in IVF couples compared to patient populations and the average population. In successful IVF couples, positive affectivity decreased, and negative affectivity increased in women until the time of embryo transfer. This was accompanied by an increase in positive affectivity in men, which remained until the time of the pregnancy test and provided emotional support to their partner. These results were confirmed by changes in the levels of depression.Conclusion Our study suggests the importance of couplesʼ emotional dynamics for having a child and an association between couplesʼ emotional reactions during IVF cycles and treatment success.
Keywords: infertility; assisted reproductive technology (ART); positive and negative affectivity; depression; anxiety